The influence of knowledge related to innovative performance - Leiva, Juan Carlos (2018)
Purpose. This paper aims to assess knowledge relatedness as a possible determinant of business innovation performance. Knowledge relatedness is understood as the degree of similarity between a firm’s knowledge and that of its parent, i.e. the company that the entrepreneur leaves to establish his or her own firm. Innovation performance results from the competitive position that the company achieves through its management of new products and services on the market. Design/methodology/approach. For the empirical work, the authors used a database composed of 356 entrepreneurs who established recently their own business in Costa Rica: people who stopped working in multinational companies in Costa Rica and created their own businesses, and people who created their own businesses simultaneously as the former employees of multinationals. Findings. This paper reports a positive and significant correlation between knowledge relatedness and innovation performance for a number of young firms. Originality/value. This paper presents the fact of including knowledge relatedness as a research topic linked to business innovation. Doi: https://doi.org/10.1108/JEFAS-11-2017-0106